EFEKTIVITAS PENGGUNAAN MEDIA YOUTUBE BERBASIS VARIOUS APPROACHES DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS - Yusri Yusri; Ana Rosida; Jufri Jufri; Mantasiah R (Makassar State University, 2018)
The purpose of this study was to determine the effectiveness of using youtube media based on various approaches in improving the learning motivation of English learners. This research is a classroom action research. Data collection techniques used in this study consisted of observations and questionnaires. The subjects in this study were 35 people. This research was carried out in two cycles, each meeting held two meetings. In the initial test, the average learning motivation was 33.74, in the first cycle was 41.25 and in the second cycle was 48.28. Therefore, if we compare it from the initial test to the second cycle test. There is an increase of 14.54. This shows that the use of youtube media has an effect on increasing students' motivation to learn English.